High-Pressure Structural Investigation of Anomalous Hall Effect Compound Mn3Sn up to 9 GPa - Lingannan G.; Singh A.K.; Joseph B.; Singh S.; Arumugam S. (My University, 2025)
A systematic synchrotron high-pressure X-ray powder diffraction study of Mn3Sn up to 9 GPa is reported. In this pressure range, the crystal symmetry remains in the hexagonal P63/mmc space group, with a continuous reduction of the lattice parameters. Analysis indicates that the Mn3Sn system may have a different magnetic ground state above 4 GPa due to varying local atomic interactions. This is brought about by the slightly varying compression rate for the in-plane a- and out-of-plane c-axis, respectively, ≈−0.0235 and ≈−0.0176 Å GPa−1. The results contribute to the understanding of the crystal structure to the external continuous tuning parameter pressure, which modulates the geometrical arrangement of the atomic species in Mn3Sn, thus impacting the interesting physical properties such as the large anomalous Hall effect. © 2021 Wiley-VCH GmbH